Analisa Kapasitas Jalan Dan Derajat Kejenuhan Berdasarkan Survey Lalu Lintas Harian Rata-Rata Di Kabupaten Paser Kalimantan Timur - Rezky Anisari (P3M Politeknik Negeri Banjarmasin, 2017)
In the province of East Kalimantan, especially the city of Tana Paser, Paser Regency, has a fairly high population growth, and is a fairly dense city and it is included as a fairly developed city hence many migrants who migrate to trade or to find a job. Based on the results of the Central Bureau of Statistics recording in 2016, the population of Tana Paser city was 50,000 people which make the city of Tana Paser as the city with the largest population in the Southern part of East Kalimantan Province. To find out the traffic density level, it is necessary to analyze and survey the traffic, the results of the analysis show that the surveyed road with the highest density level or the highest Degree of Saturation (DS) is MT Haryono road with DS value of 0.494 with road capacity of 1406 , 725 SMP / hour and total of traversing current of 694,4 SMP / hour followed by road of Untung Suropati with DS equals to 0,441 with road capacity of 2134,458 SMP / hour and total of traversing current equal to 942,350 SMP / hour. For the surveyed road with the lowest density level or the lowest Degree of Saturation (DS) is the Pelopor road with DS value of 0,020 with the road capacity of 2229,323 SMP / hour and the total traversing current is only 45,100 SMP / hour; then Sungai Tuak Sultan Hasanuddin road with DS value of 0,066 with road capacity of 3305,275 SMP / hour and total traversing current only equals to 217,050 hence the road is categorized as quiet road.